OHP-032 Cost saving potential of subcutaneous administration of trastuzumab in breast cancer in Spain. (24th February 2014) - Martin, I; Lopez-Vivanco, G; Salvador, J; Porras, I; Ramirez, C
Abstract : Background: Trastuzumab SC is a new fixed-dose subcutaneous (SC) formulation which enables trastuzumab to be delivered over 5 min compared to trastuzumab IV administered over 30 min, without compromising its efficacy and safety. Potential savings include avoidance of loading dose and reduced consumption of time resources related to administration. Purpose: To quantify the cost savings from the varying doses and resources saved during full course treatments from the Spanish NHS perspective. Materials and methods: Cost analysis includes amount of drug administered considering one loading dose (8 mg/kg) plus 17 cycles (6 mg/kg) of maintenance for the IV in comparison to the 18 fixed-dose cycles for the SC administration, both based on approved labels. A standard Spanish breast cancer patient of 66 kg and current local price of trastuzumab IV (3.67 €/mg) were considered for the cost quantification. Administration- related costs derive from a previously published Time and Motion (T&M) study, which recorded the time and resources consumed for both administrations. The T&M study was carried out in 3 Spanish centres measuring healthcare personnel (HCP) active time differences and the costs were derived from average HCP salaries (2012). Results: Total difference in dose levels between the two treatment options results in a loading dose versus a maintenance dose. The cost of a loading dose compared to maintenance dose resulted into a saving of 484 € per patient which means 1.8% of the whole treatment. T&M study reported 120 € of savings for a full treatment administration per patient with trastuzumab SC. Therefore, overall this could mean 604 € of savings per patient meaning 2.2% of overall costs. These results could mean that SC is a more efficient alternative than IV administration of trastuzumab. Conclusions: Switching trastuzumab IV to a more efficient SC administration could mean significant savings for Spanish Healthcare. No conflict of interest.